2020
DOI: 10.1007/s00784-019-03075-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of microorganisms in irreversible pulpitis and primary endodontic infections with respect to clinical and radiographic findings

Abstract: Objectives The aim of this study was to evaluate the composition of microbiota of irreversible pulpitis and primary endodontic infections with respect to clinical and radiographic findings by performing cultures and 16s rDNA sequencing in Iranian patients. Material and methods In this prospective cross-sectional study, samples were collected from 41 root canals for 4 main groups of patients. Bacterial identification was performed by the polymerase chain reaction (PCR) and 16s rDNA sequencing of aerobic and ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 59 publications
0
21
1
Order By: Relevance
“…Recently, Zargar et al . [193] found 18 species in 41 root canals from patients with irreversible pulpitis. Among them, Dialister invisus , P. gingivalis , S. salivarius , T. denticola , C. albicans and HSV-1 were the ones with highest prevalence; Lysinibacillus fusiformis was detected for the first time in the root canals.…”
Section: Oral Biofilm Dysbiosis Signatures Of Common Diseasesmentioning
confidence: 99%
“…Recently, Zargar et al . [193] found 18 species in 41 root canals from patients with irreversible pulpitis. Among them, Dialister invisus , P. gingivalis , S. salivarius , T. denticola , C. albicans and HSV-1 were the ones with highest prevalence; Lysinibacillus fusiformis was detected for the first time in the root canals.…”
Section: Oral Biofilm Dysbiosis Signatures Of Common Diseasesmentioning
confidence: 99%
“…A total of seven workers [45,50,55,62,[80][81][82] used both paper points and hand files for sample collection. Only one of them [45] used cultural methods, thus the meta-analysis could not be performed, while six of them [50,55,62,[80][81][82] used PCR, and the resulting WMP was 15.6% (CI 95%: 5.8-25.4) (Fig 5).…”
Section: Resultsmentioning
confidence: 99%
“…A total of seven workers [45,50,55,62,[80][81][82] used both paper points and hand files for sample collection. Only one of them [45] used cultural methods, thus the meta-analysis could not be performed, while six of them [50,55,62,[80][81][82] used PCR, and the resulting WMP was 15.6% (CI 95%: 5.8-25.4) (Fig 5). Thirteen studies only included teeth presenting periapical lesion, with a WMP of 5.4% (CI 95%: 2.2-8.6) for cultural studies [45,47,48,51,52,57,58,65,66,72] (Fig 6) and 18.7% (CI 95%: 2.9-34.5) for molecular studies [55,64,72,78] (Fig 7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the long-standing concept of pulp tissue necrosis as the main contributing factor for periapical lesions, there has been a growing body of evidence that inflamed vital dental pulps are capable of causing apical periodontitis (AP) ( 3 , 4 ). Studies have shown that AP can be associated with irreversible pulpitis (IP); a condition defined as an immunological response of dental pulp tissue ( 5 , 6 ) to the inflammation caused mainly by microorganisms and/or their by-products ( 7 , 8 ), which could result in local changes in pulp/periapical connective tissues ( 9 , 10 ).…”
mentioning
confidence: 99%